STRATEGIES OF TEACHING SPEAKING IN ENGLISH TO DESA BAHASA SRAGEN’S STUDENTS - Novita Indah Purwaningsih; Agus Wijayanto; Ngadiso Ngadiso (Siliwangi University, 2019)
This research aims to find out the teachers’ strategies of teaching speaking. To reach the goal, a case study on two teachers is used in this research. The participants of this research are two teachers in Desa Bahasa Sragen. The researcher is interested to conduct the research there because it offers a program called ten days English acceleration program. It claims that the students will be able to speak English fluently after joining the program.. The researcher used and the teachers’ interview to collect the data. The finding shows that there are three strategies are used at Desa Bahasa Sragen, they are: cooperative activities, creative task and drilling. The findings of this research are expected to be beneficial for the teachers on conducting the English teaching learning process, especially in teaching speaking in formal school.